The girl from everywhere - Heilig, Heidi (New York, NY : Greenwillow Books, an imprint of HarperCollinsPublishers, 2016)
Sixteen-year-old Nix has sailed across the globe and through centuries aboard her time-traveling father's pirate ship, but when he gambles with her very existence, it all may come to an end
Accelerated Reader
Accelerated Reader/Renaissance Learning
Keywords: Pirates -- Juvenile fiction; Time travel -- Juvenile fiction; Fantasy; Time travel -- Fiction; Pirates -- Fiction; Fathers and daughters -- Fiction; Young adult fiction; Fantasy fiction; Fantasy fiction; Fantasy; Maps